2018
DOI: 10.29252/jrh.8.6.513
|View full text |Cite
|
Sign up to set email alerts
|

Group training based on acceptance-commitment approach for improving quality of life and reducing anxiety among diabetic women

Abstract: The Comorbidity of diabetes with psychological disorders negatively intensifies the symptoms of diabetic patients, reduces their response to treatment, decreases their life quality and consequently increases their mortality rate. The present study was conducted to investigate the effectiveness of group training based on acceptance and commitment in improving quality of life and reducing anxiety in diabetics. The present controlled experimental study was conducted using pretests and posttests. The statistical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Various studies have confirmed the relationship between lifestyle and depression [18][19][20][21][22][23]. Cabello et al [23] showed that unhealthy lifestyles and depression are positively related in emerging countries.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Various studies have confirmed the relationship between lifestyle and depression [18][19][20][21][22][23]. Cabello et al [23] showed that unhealthy lifestyles and depression are positively related in emerging countries.…”
Section: Introductionmentioning
confidence: 96%
“…This position is associated with the individual's goals, dreams, criteria, and priorities. The definition encompasses three components of objective welfare and satisfaction, functional status, and contextual factors, considering that the first two overlap with mental health [20]. QoL is characterized by physical health, mental health status, degree of independence, social relationships, and personal beliefs, along with the relationship between these factors and the environment [21,22].…”
Section: Introductionmentioning
confidence: 99%